Entropy solutions of Dirichlet problem for a class of nonlinear elliptic fourth order equations with L¹-data - Kovalevsky, A.A. (Нелинейные граничные задачи, 1999)
We consider the question on solvability and uniqueness of entropy solutions of Dirichlet problem for a class of nonlinear elliptic fourth order equations with L¹-right-hand sides. We restrict ourselves with equations of the fourth order, but it is not so signicant.